Strategi Bertahan Hidup Rumah Tangga Nelayan di Kecamatan Galesong Utara Kabupaten Takalar - Maisarah Munirah Latief; Hasriyanti; Sartina (PT. Lontara Digitech Indonesia, 2024)
This study aims to: 1) identify opportunities Bontolebang fishermen household to maintain viability, 2) knowing the strategy of households of fishermen in order to survive through diversification of work. The research is a qualitative ethnographic. Data collection done by observation, interviews, and documentation. Analysis of the data using the methods the analysis of qualitative data through stages of reduction, data presentation and conclusion. The results of the study indicate that the strategy pursued is that adaptation strategies, and diversification strategy work through empowering women fishers and Female Head of Household (WKRT) fishing both related to fishering activities, as well as outside it. Diversification of employment opportunities depending on the resources available in the village of Bontolebang, so the potential resources optimized in diversified alternative jobs. Each fishing village has the characteristics of the natural environment which is not the same. Fishing activities for fishermen household is an activity that is speculative, therefore, fishermen who sail can not be ascertained generate revenue. Division of labor system of coastal communities and the lack of certainty of income domestic fishermen, has put women as one of the pillars supporting household necessities of life.